Agreement, history, and Obolo: A reply to Connell - Bennett, Wm. (Stellenbosch Papers in Linguistics Plus, 2016)
Connell’s (2015, this volume) reply to Bennett (2014) raises interesting points on a number of counts. The aim of this short paper is to explore how these points relate to facets of a bigger picture, both of how Obolo came to have its nasal agreement pattern, and how such long-distance agreements can arise in general.